Integration of Remote and Virtual Laboratories in the Educational Process - Wuttke, Heinz-Dietrich; Hamann, Marcus; Henke, Karsten (International Journal of Online and Biomedical Engineering (iJOE), 2015)
This paper describes a new holistic approach to integrate remote and virtual laboratories in the educational process. Aim of the integration is to test students’ knowledge not only on lower levels as usual multiple choice tests and the like are doing, but also on higher-order thinking skills. Based on these tests the students should get a detailed feedback about their strengths, weaknesses or mis-conceptions. Therefore Learning Analytics methods are applied to a database, storing learning activities of the students during their online work- phase in the educational process. The paper discusses the actual approach as well as the architecture of a prototype implementation.